The Effect of the Problem-Based Learning Model Assisted by the Kahoot Application on the Understanding of Concepts Related to the Nervous System in High School Students - Khairunnisah, Tivany; Rasyidah, Rasyidah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
The comprehension of concepts is crucial in educational activities and serves as the basis for achieving learning outcomes. However, students often encounter difficulties when it comes to understanding biological concepts, especially those related to the nervous system. This study aims to evaluate the impact of using the Problem-Based Learning model, with the support of the Kahoot application, on students’ understanding of concepts related to the nervous system. The research design employed a Quasi Experiment approach, utilizing a Two Group Pretest and Posttest Design. Cluster random sampling was used to select the participants. A 20-question multiple-choice test was employed as the research instrument to measure conceptual understanding. Descriptive analysis techniques, including the calculation of mean, median, mode, and standard deviation, were employed for data analysis. Prior to hypothesis testing, normality and homogeneity tests were conducted to ensure data validity. An independent t-test was utilized for hypothesis testing. The descriptive analysis demonstrated that the average posttest score in the experimental group was 81.09, compared to 54.53 in the control group, indicating higher scores in the experimental group. The results of the t-test (2-tailed) yielded a significant value of 0.000 < 0.05, leading to the rejection of the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). This suggests that the Problem-Based Learning model, in conjunction with the Kahoot application, has a positive impact on students’ understanding of concepts.